THE EFFECTIVENESS OF USING NATURAL PHENOMENON VIDEOS TO IMPROVE LEARNING OUTCOME ON PRESSURE MATERIALS IN SMP - Achmad Fatoni Azis; Indrawati Indrawati; Iwan Wicaksono (Journal of Science Education Research, 2020)
The use of media in learning science is still rarely used which affects students’ perception that science is a difficult subject, and results in low students’ learning outcomes. Using natural phenomena videos is a medium used to facilitate students in learning science. The purpose of this study was to describe the effectiveness of using natural phenomenon videos to improve the learning outcomes of pressure material in junior high school (SMP). This research used a quantitative descriptive study that aimed to see the effect of using media in improving the students’ learning outcomes. The design of the study used one group pre-test-post-test design. The data collection technique was a test of learning outcomes, where N-Gain used for the calculation analysis of learning outcomes. The results showed an increase in students’ learning outcomes after treated using natural phenomena videos on pressure material learning by 0.5977 that included in the medium category. Thus, learning using natural phenomena videos was effective in improving the students’ learning outcomes on pressure material in the medium category.